The Solitary Voice of Dissent : Using Foucault and Giddens to Understand an Existential Moment - Kay, Martin (Vernon series in critical perspectives on social science., 2016)
This book urges respect for solitary dissent rather than censure. It equips a wide audience to understand what previously seemed unimaginable, much less comprehensible. It shows the reader how to reach beyond those first conclusions and into the heart of the matter. The lone voice explains that something has been hidden away, something which the individual now dissenting can no longer acquiesce in. It raises the possibility that more may be seriously wrong. Those who need to understand range from academics, to researchers, to managers, to elected representatives, to journalists. We all have an.